Perancangan Sistem Informasi Absensi Asisten Lab Berbasis Android pada Universitas Pamulang - Alvino Octaviano; Sofa Sofiana; Satrio Pandita Priyadi (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2020)
Fingerprint recognition with distance-based optimization and pattern matching, "international conference on signal processing, communication, power, and data management systems on attendance paper makes it very difficult to log absent and absent assistants. In this case Change of attendance records to save. in a digital-based information system database. Meanwhile, fingerprint attendance methods or methods have been used on cellphones. Record attendance. Method makes applications that support digital attendance with Android. Android is an operating system application for mobile phones based on Linux. Android offers developers an open platform where they can create their own applications used by various mobile devices.